MODEL PENDIDIKAN KARAKTER DI MASYARAKAT - Agus Sopian (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
This study aims to examine the development of a character education model in society. This research uses the library research method, which is research conducted through data collection or scientific writing with the object of research or library data collection. The results of the analysis show that character is a way of thinking and behaving that is characteristic of each individual to live and work together, both within the sphere of family, society, nation and state. Values ​​in community-based character education can come from religion, Pancasila, culture, and the goals of national education. The development of a model that can be used in the practice of character education in society, especially in government institutions, social institutions, and in public spaces, is a model of education through the process of teaching, modeling, and habituation, motivating, and enforcing rules